Role of Filler Content and Morphology in LLZO/PEO Membranes - Din, Mir Mehraj Ud; Häusler, M.; Fischer, S. M.; Ratzenböck, K.; Chamasemani, F. F.; Hanghofer, I.; Henninge, V.; Brunner, R.; Slugovc, C.; Rettenwander, D. (Frontiers in Energy Research, 2021)
Polymer electrolytes containing Li-ion conducting fillers are among the extensively investigated materials for the development of solid-state Li metal batteries. The practical realization of these electrolytes is, however, impeded by their low Li-ion conductivity, which is related to the filler and the interplay between the filler and the polymer. Therefore, we performed an in-depth analysis on the influence of the filler content (0, 10, and 20 wt%) and filler morphology (particles and nanowires) on the electrical and electrochemical properties of the PEO-based composite electrolyte using a wide spectrum of characterization techniques, such as 3D micro-X-ray computed tomography, cross-sectional scanning electron microscopy, X-ray diffraction, and differential scanning calorimetry, impedance spectroscopy, and galvanostatic cycling. The studies reveal that the filler materials are well distributed within the membranes, without any indications for the formation of agglomerates. For 10 wt% filler, a decrease in the crystallinity compared to PEO was observed, in contrast to 20 wt% filler showing an increase in crystallinity. Impedance spectroscopic studies on the Li-ion conductivity of the membranes have shown that the change in the Li-ion conductivity is solely related to the change in the crystallinity, rather than to the participation of LLZO as an active transport mediator. The PEO membranes containing 10 wt% LLZO have been tested in terms of their rate capability in symmetrical Li cells by galvanostatic cycling. A critical current density of up to 1 mA cm−2 at 60°C was observed.